Interdisciplinary Researches for Cultural Heritage Conservation - Saiz-Jimenez, Cesareo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue on Interdisciplinary Research for Cultural Heritage Conservation in Applied Sciences aims to bring together some of the latest researches in this field. A total of 10 papers focusing on different aspects of cultural heritage were published on the topics: rock art, mural paintings, stone monuments, stained-glass windows, environmental sensors, historic infrastructures, and analects of Confucius.